Non-invasive sampling procedure revealing the molecular events at different abutments of bone-anchored hearing systems–A prospective clinical pilot study - Johansson, Martin L.; Omar, Omar; Trobos, Margarita; Jonhede, Sofia; Peters, Hanna; Hultcrantz, Malou; Thomsen, Peter (Frontiers in Neuroscience, 2022)
Purpose: To investigate the molecular activities in different compartments around the bone-anchored hearing system (BAHS) with either electropolished or machined abutments and to correlate these activities with clinical and microbiological findings. Methods: Twelve patients received machined or electropolished abutments after implant installation of BAHS. Peri-abutment fluid and tissue were collected from baseline to 12 months. Gene expression of cytokines and factors related to tissue healing and inflammation, regeneration and remodelling, as well as bacterial recognition were determined using quantitative-polymerase chain reaction (qPCR). The clinical status was evaluated using the Holgers scoring system, and bacterial colonisation was investigated by culturing. Results: The gene expression of inflammatory cytokines (IL-8, IL-1 and IL-10) and bacteria-related Toll-like receptors (2 and 4) was higher in the peri-abutment fluid than at baseline and peri-abutment tissue. Conversely, the expression of genes related to tissue regeneration (Coll1a1 and FOXO1) was higher in both tissue samples than in the peri-abutment fluid. Electropolished abutments triggered higher expression of inflammatory cytokines (IL-8 and IL-1) (in peri-abutment fluid) and regeneration factor FOXO1 (in peri-abutment tissue) than machined abutments. Several cytokine genes in the peri-abutment fluid correlated positively with the detection of aerobes, anaerobes and Staphylococcus species, as well as with high Holger scores. Conclusion: This study provides unprecedented molecular information on the biological processes of BAHS. Despite being apparently healed, the peri-abutment fluid harbours prolonged inflammatory activity in conjunction with the presence of different bacterial species. An electropolished abutment surface appears to be associated with stronger proinflammatory activity than those with a machined surface. The analysis of the peri-abutment fluid deserves further verification as a noninvasive sampling and diagnostic procedure of BAHS.